Lubricity performance of non-ionic surfactants in high-solid drilling fluids: a perspective from quantum chemical calculations and filtration properties - Kania, Dina; Yunus, Robiah; Omar, Rozita; Abdul Rashid, Suraya; Mohamed Jan, Badrul; Aulia, Akmal (Elsevier BV, 2021)
Quantum chemical calculations and mud filtration analysis were used to assess the performance of three types of non-ionic surfactants as lubricating additives in synthetic-based drilling mud (SBM) contaminated with drilled solids. High solid contaminants can have an impact on mud lubricity and can contribute to thicker a mud cake. Experimental results showed that all non-ionic surfactants reduced the coefficient of friction (COF) of mud by approximately 27%. Quantum chemical parameters and molecular electrostatic potential (MEP) provided further insights into the interaction between non-ionic surfactants and metal surfaces. MEP indicated the most lubricious non-ionic surfactant based on polar sites and the electron density distribution. Dipole moment represented the dipole interaction between the polar head of non-ionic surfactant with the metal surface of the drilling tools. Filtration tests showed that despite solid contamination, non-ionic surfactants decreased the fluid loss by 20% due to better solid dispersion in the mud. The mud cake formed was thinner, which may reduce the differential pressure sticking tendency. XRD and SEM observations of the mud cake confirmed the presence of non-ionic surfactants layer adsorbed to the solid particles of SBM. The adsorbed non-ionic surfactants could contribute to a higher lubricity of mud cake, thus minimizing friction during drilling.